2003
DOI: 10.1007/bf02988451
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of response to radiation therapy for human tumor xenografts using99mTc-HL91 (4,9-diaza-3,3,10,10-tetramethyldodecan-2,11-dione dioxime)

Abstract: 99mTc-HL91 uptake in tumors did not always relate to their sensitivities to radiation therapy. Sequential 99mTc-HL91 imagings post irradiation showed that the increase in 99mTc-HL91 uptake in tumors predicted a poor response to radiation therapy, and that a decrease or no change suggested that radiation therapy would be effective. Monitoring by 99mTc-HL91 imaging is a good tool to predict the radiosentivities of tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The labeling process is simple with mild reaction conditions (45). After the labeling, separation and purification of free iodine and iodine binding peptides must be conducted, which takes a long time, and because the iodine connected to tyrosine is easy to fall off in the body and 123 I is expensive, the application of iodine-labeled LHRH is rare (46,47). …”
Section: Discussionmentioning
confidence: 99%
“…The labeling process is simple with mild reaction conditions (45). After the labeling, separation and purification of free iodine and iodine binding peptides must be conducted, which takes a long time, and because the iodine connected to tyrosine is easy to fall off in the body and 123 I is expensive, the application of iodine-labeled LHRH is rare (46,47). …”
Section: Discussionmentioning
confidence: 99%
“…This result was not in accordance with the past experimental study. The experimental study of Suzuki et al demonstrated that the increase of 99 Tc m -HL91 uptake in tumors post irradiation predicted a poor response to radiation therapy, and that a decrease or no change suggested that radiation therapy would be effective [10] . The mechanisms of the T/N rising during radiotherapy may be: (1) Radiotherapy would consume oxygen in tumor tissue, and the oxygen pressure in tumor tissue would decrease to the lowest spot as soon as the radiotherapy was ended [11,12] .…”
Section: Discussionmentioning
confidence: 99%
“…99m Tc-HL91 has also been used in clinical studies as a potential tracer to detect hypoxic myocardium. Information on the uptake of this marker, correlated with blood parameters, permits a measurement of the severity of hypoxia [102][103][104].…”
Section: N-chelating Ligandsmentioning
confidence: 99%